Field Trial on the Control of Flies in Cattle by Spraying Aqueous Extract of Leaves and Seeds of Moringa Oleifera - Gonzalez-Alvarez, Vicente Homero; Alvarado-Rodriguez, Gabriela; Reachi-Guzman, Esdras; Dolores-Rafael, Joel; Moreno-Melo, Heladio; Saavedra-Jimenez, Luis Antonio (International Journal of Veterinary Sciences Research, 2022)
Cattle flies are external, blood-sucking parasites. Their control can be done by using repellents from plant extracts. The objectives of the research were, to determine the number of flies that infest cattle and to evaluate how long the aqueous extract of leaves and seeds of M. oleifera took to make effect. Through the study, fly counts on the wither or hump region were taken between 8:00-9:00 am and 5:00-6:00 pm. To obtain the aqueous extract, 2.5 kg of leaf and seed powder were used, diluted in 20 L of distilled water. The solution was left to stand for 24 h in a dark room. With the liquid obtained, four clinically healthy bovines, two females of the Gray Brahman and Suizbu breeds and two bulls of the Guzerat and Red Brahman breeds, were sprayed until the aqueous extract runoff. Once the treatment was applied, the fly count was performed on the surface of the animals. During the three days of the study, a total of 1,256 flies were counted in the four animals, with an average of 608 flies on days 1 and 3 of the experiment, while on day 2 it decreased to 52 flies, with an average of 10 flies in the morning. and 42 in the afternoon. The spraying with the extract of leaves and seeds prevented the flies from landing on the animals; however, a long-lasting repellent effect was not observed.